A prospective comparative study in the management of Neer’s type II and type III proximal humerus fracture with proximal humerus nail versus proximal humerus internal locking system - R., Ramesh; Ahamed, Ameen (International Journal of Research in Orthopaedics, 2017)
Background: Proximal humerus fractures account for approximately 4-5 % of all the fractures and are next in occurrence to hip fractures and distal radius fractures in elderly population. Methods: A prospective study of 40 patients with Neer’s type II and type III proximal humerus fracture, among which 20 were treated with proximal humerus nail and 20 with proximal humerus internal locking system at two Hospitals attached to J.J.M Medical College Davangere, Karnataka, India between September 2015 to December 2016. At final follow up results were assessed with constant shoulder scoring system. Results: In the PHN group, 8 patients (40%) showed excellent outcome, 8 patients (40%) showed good outcome and 4 patients (20%) showed fair outcome. Among the PHILOS group, 12 patients (60%) showed good outcome, 6 patients (30%) showed fair outcome and 02 patients (10%) with poor outcome. Conclusions: Proximal humerus nail for Neer’s type II and type III proximal humerus fracture has better results compared to proximal humerus locking plate system with increased range of movements and restoring better shoulder biomechanics.